HYFI: Hybrid filling of the dead‐time gap for faster zero echo time imaging. (23rd February 2021) - Froidevaux, Romain; Weiger, Markus; Rösler, Manuela B.; Brunner, David O.; Pruessmann, Klaas P.
Abstract : The aim of this work was to improve the SNR efficiency of zero echo time (ZTE) MRI pulse sequences for faster imaging of short‐ T 2 components at large dead‐time gaps. ZTE MRI with hybrid filling (HYFI) is a strategy for retrieving inner k‐space data missed during the dead‐time gaps arising from radio‐frequency excitation and switching in ZTE imaging. It performs hybrid filling of the inner k‐space with a small single‐point‐imaging core surrounded by a stack of shells acquired on radial readouts in an onion‐like fashion. The exposition of this concept is followed by translation into guidelines for parameter choice and implementation details. The imaging properties and performance of HYFI are studied in simulations as well as phantom, in vitro and in vivo imaging, with an emphasis on comparison with the pointwise encoding time reduction with radial acquisition (PETRA) technique. Simulations predict higher SNR efficiency for HYFI compared with PETRA at preserved image quality, with the advantage increasing with the size of the k‐space gap. These results are confirmed by imaging experiments with gap sizes of 25 to 50 Nyquist dwells, in which scan times for similar image quality could be reduced by 25% to 60%. The HYFI technique provides both high SNR efficiency and image quality, thus outperforming previously known ZTE‐based pulse sequences, in particular for large k‐space gaps. Promising applications include direct imaging of ultrashort‐ T 2 components, such as the myelin bilayer or collagen, T 2 mapping of ultrafast relaxing signals, and ZTE imaging with reduced chemical shift artifacts. Abstract : HYFI is a strategy for retrieving inner k‐space data missed during the dead‐time gap arising from radio‐frequency excitation and switching in ZTE imaging. It performs hybrid filling of the inner k‐space with a small single‐point‐imaging core surrounded by a stack of shells and provides both high SNR efficiency and image quality, thus outperforming previously known ZTE‐based pulse sequences, particularly at large dead‐time gaps. Promising applications include direct imaging of ultrashort components, such as the myelin bilayer or collagen.